1985
DOI: 10.1002/jmv.1890160410
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytomegalovirus in urine samples by enzyme‐linked immunosorbent assay

Abstract: An enzyme-linked immunosorbent assay (ELISA) was developed for the detection of cytomegalovirus (CMV) in urine using monoclonal antibodies directed against CMV as a capture for viral antigen. The assay was capable of detecting virus at 10(2.3)TCID50/ml as determined by titration of stock virus, strain Ad169. The assay was found to have a sensitivity of 65% and a specificity of 100% when 73 coded stored urine specimens were examined. Assuming that the poor sensitivity was due to loss of antigen following storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…McKeating et al (1985) reported that their ELISA for the detection of HCMV failed to detect the virus in fresh urine samples, but that upon storage at 4 °C for 1 to 2 weeks initially negative samples became ELISA-positive. They postulated the presence of an inhibitory substance in fresh urine which might be destroyed upon storage, and subsequently McKeating et al (1986) identified fl2m as such an inhibitor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…McKeating et al (1985) reported that their ELISA for the detection of HCMV failed to detect the virus in fresh urine samples, but that upon storage at 4 °C for 1 to 2 weeks initially negative samples became ELISA-positive. They postulated the presence of an inhibitory substance in fresh urine which might be destroyed upon storage, and subsequently McKeating et al (1986) identified fl2m as such an inhibitor.…”
mentioning
confidence: 99%
“…One factor unexplained by the electron microscopy evidence regarding non-involvement of envelope proteins in fl2m binding was the report by McKeating et al (1985) of failure to detect HCMV in fresh urine samples by means of their ELISA system which utilized monoclonal antibodies said to be directed against HCMV glycoproteins. Their assumption was that fl2m in urine bound to the viral glycoproteins thus inhibiting their attachment to the solid phase.…”
mentioning
confidence: 99%
“…Second, it is well recognized but to our knowledge not previously published, that CMV in urine cannot be neutralized by antisera with good neutralizing activity against CMV grown in cell culture. Third, we have recently reported that CMV in urine specimens cannot be captured onto a solid phase by CMV-specific monoclonal antibodies which can capture CMV grown in vitro (McKeating et al, 1985), suggesting some differences in surface antigens between viruses from the two sources.…”
Section: Introductionmentioning
confidence: 99%
“…Second, it is well recognized but to our knowledge not previously published, that CMV in urine cannot be neutralized by antisera with good neutralizing activity against CMV grown in cell culture. Third, we have recently reported that CMV in urine specimens cannot be captured onto a solid phase by CMV-specific monoclonal antibodies which can capture CMV grown in vitro (McKeating et al, 1985), suggesting some differences in surface antigens between viruses from the two sources.We have shown that urine contains a host protein, f12 microglobulin (flzm) which, at physiological concentrations, inhibits the capture of cell culture-grown CMV by virus-specific monoclonal antibodies (McKeating et al, 1986). We postulated that this inhibition was due to the binding of fl2m to the virus masking the viral antigenic determinants.…”
mentioning
confidence: 99%
“…For the rapid diagnosis of active CMV infection, several attempts have been made. Those included (i) the detection of virus particles by electron microscopy (20), (ii) the detection of viral antigens by enzyme-linked immunosorbent assay (ELISA) (17,24), immunofluorescence staining (1,8,13,14,22,26,31,33), iminunoperoxidase staining (12,25,30), or dot immunoassay (23,34), and (iii) the detection of viral nucleic acid by DNA hybridization (4,12,22,25,27,28,32) or polymerase chain reaction (PCR) (11). Among those attempts, the detection of viral antigens in cell culture with monoclonal antibodies against IEA or EA is a rapid, sensitive and the most practical method to identify the CMV isolates.…”
mentioning
confidence: 99%